Teachers’ emotions in the time of COVID: Thematic analysis of interview data reveals drivers of professional agency - Porter, Karen; Miles, Paula Jean; Donaldson, David Ian (Frontiers in Psychology, 2022)
Purpose. We explored two complex phenomena associated with effective education. First, teacher’s professional agency, the volitional actions they take in response to perceived opportunities, was examined to consider individual differences in its enactment. Second, “strong” emotions have been proposed as important in teaching and learning, and we wished to clarify which basic emotions might be involved, besides curiosity, which is a known emotional factor in engagement in teaching. We also explored how agency and basic emotions might be related. Approach. Thirteen teachers working in Scottish secondary schools were interviewed at the start of the covid pandemic in 2020 to discuss relevant feelings, thoughts and actions arising from unprecedented changes in their lives and professional practices. Thematic analysis was used to identify aspects of agentic behaviour and basic emotions expressed. Findings. Teacher agency was expressed through adaptability, collective agency, constrained agency, and non-action. Four basic emotion percepts were identified, which we label as “CARE”, “CURIOSITY”, “COOPERATION” and “CHALLENGE”. Originality. We extend the definition of agency to include volitional non-action as a response to opportunity. In contrast to prior research emphasising emotions as an outcome of volitional behaviour, we explore emotions preceding agency. We develop four theoretical propositions related to teacher emotions.1) Four emotion percepts substantially influence teachers’ voluntary motivated behaviour. 2) The amount, and proportion of emotions experienced varies between individual teachers. 3) The four percepts are experienced concurrently or in rapid succession in engaged teaching contexts. 4) Professional experience and specific situational factors also influence teachers’ behavioural choices. For future consideration, we suggest that awareness of emotion percepts may encourage both teachers’ engagement and their professional agency for the benefit of their pedagogical practice and outcomes for their students.